Apps for remote theater teaching: Avatar, deepfake, padlet and other experiments (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This text deals with the practices of a theater teacher, carried out in State Schools of Minas Gerais in an emergency remote teaching regime, imposed by the Covid-19 sanitary crisis. A brief discussion on the use of technologies applied to education will be presented, as well as reflections on the role of theater in school and on what theater can do in this context of remote classes. The report accompanies an critical reflection, and demonstrations through images, texts and videos. Applications became a real possibility, and were used in various practices as something capable of integrating aspects of the theatrical experience itself.
Keywords: Theater; Pandemic; Remote study; Technology